If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = r + -8 Reorder the terms: -15 = -8 + r Solving -15 = -8 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. -15 + -1r = -8 + r + -1r Combine like terms: r + -1r = 0 -15 + -1r = -8 + 0 -15 + -1r = -8 Add '15' to each side of the equation. -15 + 15 + -1r = -8 + 15 Combine like terms: -15 + 15 = 0 0 + -1r = -8 + 15 -1r = -8 + 15 Combine like terms: -8 + 15 = 7 -1r = 7 Divide each side by '-1'. r = -7 Simplifying r = -7
| 7+2(x-3)-4x= | | y+1(9+24)-28=96 | | 5x+20=5x-18 | | 10+a=26 | | x(7x+5)-x(x)(x)=0 | | 5x^2+10x+8y^2-48y+37=0 | | 2(113-2c)+4c=226 | | 20+10x-(8x-12)=68 | | .03x+.07(18000-x)=90 | | 4k-(-6)=-2-(-16)-(-2) | | 6n-.7=11 | | 10+n=25 | | -18x^2+51x+8=0 | | X^2+6x+64=48 | | 9x^4-64=0 | | 4c^2+7x-15=0 | | 15+n=6 | | 3x^4-7x^2=0 | | (4x+2)-x=(2x-10) | | 9(2+v)+35v=14v | | .5x(x+4)=16 | | 69=12 | | 2a+4b=226 | | 8(4+v)+34v=14v | | -2.3q+16=-5q-3 | | x^2+6x-24.01=0 | | 10*x+4=12*x-16 | | 3+2(x-1)=4x | | 3+2n-6=25 | | 8z+11=7z+5 | | 4(12n-6)=6(-4+5n)+18n | | 2x-2.8-2.4x+2.6x-5= |